2015
DOI: 10.33119/kszpp.2015.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Instytucjonalne bariery w realizacji polityki publicznej

Abstract: Bariery w realizacji polityki publicznej pojawiają się na długo przed przystąpieniem do jej wdrażania. Wadliwe instytucje utrudniają właściwą identyfikację problemów i formułowanie polityki. Głównym problemem jest brak określenia centrum decyzyjnego, będącego głównym podmiotem odpowiedzialnym za tworzenie polityki publicznej.Funkcjonalne splecenie władzy ustawodawczej i wykonawczej pozbawia parlament wpływu na kształt polityki publicznej. Również rząd nie pełni przypisanej mu funkcji prowadzenia polityki. Dane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…6 Dudzinska et al (2001) have explained in their study how progressive hypoxia results in impairment of the oxidative resynthesis of ATP and increased degradation of purine nucleotides exercise with increasing intensity leads to increased concentration of uric acid. 7 Alina Gailiūnienė reported exercise-induced statistically insignificant (p > 0.05) increases in the blood parameters of nitrogen compounds (Creatinine, urea, total protein and uric acid) and suggested that it could be due to the common phenomenon of the physical stress and catecholamine effects. 8 In this present study there is significant difference between urea and uric acid level in pre and post exercise conditions in males although in females no significant alteration seen in pre and post exercise levels.…”
Section: Discussionmentioning
confidence: 99%
“…6 Dudzinska et al (2001) have explained in their study how progressive hypoxia results in impairment of the oxidative resynthesis of ATP and increased degradation of purine nucleotides exercise with increasing intensity leads to increased concentration of uric acid. 7 Alina Gailiūnienė reported exercise-induced statistically insignificant (p > 0.05) increases in the blood parameters of nitrogen compounds (Creatinine, urea, total protein and uric acid) and suggested that it could be due to the common phenomenon of the physical stress and catecholamine effects. 8 In this present study there is significant difference between urea and uric acid level in pre and post exercise conditions in males although in females no significant alteration seen in pre and post exercise levels.…”
Section: Discussionmentioning
confidence: 99%
“…Problematyka konfliktów społecznych w exposés polskich premierów z lat [2007][2008][2009][2010][2011][2012][2013][2014][2015][2016][2017] Strona 7 z 19 znajduje potwierdzenie w opracowaniach naukowych i eksperckich (Dudek, 2016, s. 603;Dudzińska, 2015;Jasiecki, 2016). Autorzy raportu pt.…”
Section: Mateusz Pękalaunclassified
“…W 1945 r. szacowano, że w mieście pozostało ok. 30% zabudowy, nie działała elektrownia, gazownia 21 . Brak infrastruktury znacznie utrudniał zasiedlenie jeszcze w 1949 r. 22 Z kolei od lat 50. XX w. obserwowane były migracje ze wsi rejonu morąskiego do różnych miast oraz powolny spadek liczby urodzeń na tym terenie 23 .…”
unclassified